Challenges of Special Education Teachers in Teaching Deaf Students: A Case Study in a Special School - Trio wahyudi; Feri Aprillah; St. Aisyah; Lailatul Qadriyah (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2025)
This study examines the challenges faced by special education teachers in teaching deaf students within inclusive educational settings. Children with hearing impairments require adaptive and individualized instructional approaches due to their limitations in verbal communication and language development. The objective of this research is to explore and identify the specific challenges encountered by a teacher at a special school (SLB Dharma Wanita Sumenep) and to understand the strategies used to address them. This study employs a qualitative method with an intrinsic case study approach, focusing on a single teacher as the research subject. Data were collected through in-depth interviews and direct observations, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal several key challenges, including communication barriers, limited learning media and instructional materials, lack of professional support, dependence on parental collaboration, limited facilities, and the need for individualized learning approaches. Communication difficulties emerge as the most dominant issue, requiring teachers to master sign language and adapt teaching strategies. In conclusion, despite various constraints, teachers demonstrate strong commitment and adaptability in supporting deaf students. The study highlights the importance of collaboration, adequate resources, and flexible pedagogical practices in achieving effective inclusive education.